Care demands on mothers caring for a child with Down syndrome: Malaysian (Sarawak) mothers' perspectives - Chan, Kim Geok; Khatijah, Abdullah Lim; Ling, How Kee (Wiley Publishing Asia Pty Ltd, 2015)
This paper examines the experiences of mothers caring for a child with Down syndrome in the Malaysian (Sarawak) context. Qualitative interviews were conducted with 26 biological mothers of children with Down syndrome aged 18 years and below. They were accessed through selected child health clinics, community-based rehabilitation centres and schools using purposive sampling within two regions in Sarawak, one of the two Borneo States of Malaysia. Major themes emerging within the context of care demands were children’s health, developmental delays, daily needs and behaviour issues. The insights obtained into the care demands experienced by mothers of children with Down syndrome have several implications for practice by care professionals.